The lord of the rings. The war of the Rohirrim [videorecording (Blu-Ray)] - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973; Addiss, Jeffrey; Matthews, Will; Boyens, Philippa; Gittins, Phoebe (Warner Bros., 2025)
It tells the fate of the House of Helm Hammerhand, the legendary King of Rohan. A sudden attack by Wulf, a clever and ruthless Dunlending lord seeking vengeance for the death of his father, forces Helm and his people to make a daring last stand in the ancient stronghold of the Hornburg a mighty fortress that will later come to be known as Helm's Deep. Finding herself in an increasingly desperate situation, Hera, the daughter of Helm, must summon the will to lead the resistance against a deadly enemy intent on their destruction.